Implementation of Kosa Rupa Book: Drawing and Coloring of Elementary School Teachers in Pegayaman Village, Bali - Alhail, Hadi; Rubijanto, Vincensius Jovan; Musthafa, Akram; Purnama, Della; Utama, I Gusti Agung Gede Aditya (Gorga : Jurnal Seni Rupa, 2024)
Difficulty in teaching learning related to drawing from teachers to students is a problem experienced by elementary school teachers in Pegayaman Village, previous research provides information that there is one media to help teachers improve their drawing and coloring competencies, namely "kosa rupa". The purpose of this study was to implement kosa rupa in elementary school teachers in Pegayaman Village through training and mentoring. The method used is qualitative, descriptive and exploratory research design. Collection techniques through interviews, observations, and documentation. The instruments used are interview drafts, observation drafts, and documentation lists. Data validity testing is carried out by triangulation testing. Data analysis techniques use domain analysis, taxonomy, and componential. Respondents involved in the research setting were 3 teachers. The results of the research on the implementation of kosa rupa in elementary school teachers in Pegayaman Village through training and mentoring are: 1) Discussion of teaching experiences in drawing and coloring that have been applied to students, 2) Discussing and identifying problems faced by teachers, 3) Introducing and presenting kosa rupa and how it works, 4) Demonstrating kosa rupa based on aspects of composition, perspective, and color, 5) Conducting training and mentoring on the implementation of village-themed kosa rupa for teachers, 6) Conducting intensive open evaluation and reflection carried out by teachers on the results of work made based on aspects of composition, perspective, and color.